RESPONSE OF BROILER CHICKENS FED ON DIETS CONTAINING LOW LEVEL OF AFLATOXIN (B1 AND B2) AND SUPPLEMENTED WITH MYCOTOXIN BINDER - Catootjie L. Nalle; Andrijanto A. H. Angi; Max A. J. Supit; Santi Ambarwati; Ni Sri Yuliani (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
The objective of the present study was to evaluate the growth performance and feet colour of broilers fed on diets containing low level of aflatoxin (B1 and B2) and mycosorb. The experimental design was a 4 x 2 factorial randomized complete design consisting of two main factors which were aflatoxin level and mycosorb. The treatments were control diets, control diets supplemented with mycosorb, diets containing 10 ppb aflatoxin, diets containing 10 ppb aflatoxin supplemented with mycosorb, diets containing 25 ppb aflatoxin, diets containing 25 ppb aflatoxin supplemented with mycosorb, diets containing 60 ppb aflatoxin, diets containing 60 ppb aflatoxin supplemented with mycosorb. The aflatoxin levels in the experimental diets obtained by substitution the proportion of corn of the control diets with aflatoxin corn. Variables measured were feed intake (FI), body weight gain (BWG), feed conversion ratio (FCR). Except for feet colour score, the results showed that there was no interaction (P > 0.05) between aflatoxin level and mycosorb on FI, BWG and FCR of 7d- and 14 d-old-broilers. The aflatoxin level did not affect (P > 0.05) BWG, FI and FCR (7d) but it affected (P < 0.05) the FCR (14d) and feet colour of broiler. Mycosorb did not affect (P > 0.05) all parameters observed. In conclusion, except for broiler feet colour, the supplementation of aflatoxin, mycosorb and combination between aflatoxin and mycosorb in broiler diets had no effects on the growth performance of broilers during 7 and 14 day experiment. Further research is needed to evaluate the growth performance of broilers fed diets containing high level of aflatoxin.